Severe disease expression of cardiac troponin C and T mutations in patients with idiopathic dilated cardiomyopathy. - Mogensen, J; Murphy, RT; Shaw, T; Bahl, A; Redwood, C; Watkins, H; Burke, M; Elliott, P; McKenna, W (2004)
OBJECTIVES: We performed genetic investigations of cardiac troponin T (TNNT2) and troponin C (TNNC1) in 235 consecutive patients with idiopathic dilated cardiomyopathy (DCM) to evaluate prevalence of mutations and associated disease expression in affected families. BACKGROUND: Recently, mutations in sarcomeric genes have been reported in DCM. However, the prevalence, penetrance, and clinical significance of sarcomere gene mutations in large consecutive cohorts of DCM patients are poorly defined. METHODS: Mutation detection was performed by fluorescent SSCP/DHPLC analysis and direct sequencing. The functional effects of mutations on interactions within the troponin complex were assessed by a two-hybrid luciferase assay. RESULTS: A total of 43% (102 of 235) of the study cohort had familial DCM. One TNNC1 and four TNNT2 (three novel) mutations were identified in one and four families, respectively. The prevalence of TNNC1/TNNT2 mutations in familial DCM was 5% with a penetrance of 100%. A total of 21 mutation carriers were identified; 6 underwent cardiac transplantation, 5 died of heart failure, and 4 died suddenly at a mean age of 29 years, while 6 remained stable on medication. Functional studies showed significant impairment of mutated troponin interaction compared with wild-type control, indicating an altered regulation of myocardial contractility. CONCLUSIONS: Cardiac troponin C was identified as a novel DCM gene. The disease expression associated with TNNC1 and TNNT2 mutations was severe with complete penetrance. The data suggest that mutation analysis of the troponin complex in DCM patients may prove valuable in early identification of individuals with an adverse prognosis and a high risk of premature death. This may lead to improved management and survival.